Ator-professor e as práticas teatrais na educação: poéticas esponatâneas para os entre-luares do ensino médio - Péricles Davy Lima da Silva (2024)
This study presents an investigation into theatrical practices at school based on the author's trajectory, as an actor-teacher-researcher in Theater. More specifically, the starting point here is the way in which the author understands himself artistically and pedagogically and how his experiences were crossed by in-between places, especially in the context of Basic Education, High School at public schools, in the city of Fortaleza, Ceará. In this place, the author traced a path through artistic and teaching experiences, from 2013 to 2021. This study also covers his experiences in creative processes as a theater actor, with groups in the capital of Ceará. From this, a reflection is developed in dialogue with practices and studies in the field of theater and theatrical pedagogies, such as: spontaneous theater (ESS, 2014); own poetics (MACHADO, 2015); poetics for the classroom (LÍRIO, 2014), among others. In an autoethnographic exercise, the author's past practices are analyzed and interpreted, through memories of these artistic and pedagogical experiences, brought through remembrances, records in logbooks and other documents from the researcher's processes. As part and result of the research, it is shared, as an educational resource, a workshop notebook for theatrical practices, entitled Spontaneous poetics for high school in-between places, to which can have access people interested in aesthetic and poetic experiences specific to the classroom, especially for high school.